Syngenta Enogen Feed Corn Silage Containing an Alpha Amylase Expression Trait Improves Feed Efficiency in Growing Calf Diets - M. A. Johnson; T. Spore; S. P. Montgomery; W. R. Hollenbeck; R. N. Wahl; E. D. Watson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:To determine the growing calf response when fed Enogen Feed corn silage containing an alpha amylase expression trait. Study Description:Crossbred steers of Tennessee origin (n = 352) were used to determine the effects on performance when fed Enogen Feed corn silage with either Enogen Feed corn or control corn at ad libitum intake. The Bottom Line:When fed in an ad libitum fashion to growing calves, Enogen Feed corn silage improves the efficiency of feed conversion by 4.4% and average daily gain by 6.0%.
Keywords: corn silage; alpha amylase; growing calf